Legacies of Colonialism in Museum Collections : The (Un)Making of Indonesian Islam in the Netherlands - Shatanawi, Mirjam, (Arts and Archaeology of the Islamic World ;, 2025)
This groundbreaking book tells the untold story of Indonesian Islam in museums. Often overshadowed by Hindu-Buddhist art, Indonesian Islamic heritage rarely receives the attention it deserves in museum collections and exhibitions. This book unravels the historical silences rooted in Dutch colonial rule that have marginalized Indonesian Islamic material culture. Delving into the colonial archives, it traces the journey of Indonesian objects in Dutch museums, exploring their original meanings and their re-appropriation during instances of collecting, classification, interpretation and public display. Through this lens, the book addresses the enduring impacts of colonialism and offers pathways for the decolonization of museums today.